KELIMPAHAN POPULASI DAN PERSENTASE SERANGAN LALAT BUAH YANG MENYERANG TANAMAN BUAH-BUAHAN DI BALI - Astriyani, Ni Kadek Nita Karlina; Supartha, I Wayan; Sudiarta, I Putu (Journal of Agricultural Science and Biotechnology; Vol 5 No 1 (2016), 2016)
The study was conducted at the Field and in the Laboratory . Laboratory research was conducted at the Laboratory Integrated Pest and Disease Control Management, Faculty of Agriculture, Udayana University, Bali with altivial 30 meters above sea level from January to March 2014. In field, study was conducted by sampling the fruit flies attacking fruit with Purposive random sampling.The results showed that there were 6 species found in the market and fruits’ center in Bali, namely Bactrocera papayae Drew & Hancock, Bactrocera carambolae Drew & Hancock,Bactrocera umbrosa Fabricius, Bactrocera cucurbitae Coquillete, and Bactrocera albistrigatade Maijere (Diptera: Tephritidae). The spesies fruit flies attack in mango, orange, long chili, rawit chili, watermelon, cucumber, star fruit, sapodilla, nephelium, jackfruit, rose-apple and guava. The abundance of fruit flies population had a positive relationship with the persentage of fruit flies’ attack.
Keywords: Fruit flies; abundance and percentage attack